Efecto de la utilización de extractos vegetales para el control de enfermedades foliares en brócoli (brassica oleracea var. itálica) cultivado en tres localidades urbanas de Quito. - Duchimaza Angamarca, Mauricio Geovanny (2022)
The indiscriminate use of agrochemicals has led to the deterioration of the production system, causing low soil fertility and resistance to pathogens, promoting higher spending on external inputs, especially pesticides. Antecedents such as these promoted the present investigation with the objective of evaluating the effects of the vegetal extracts of thyme (Thymus vulgaris), garlic (Allium sativum), chamomile (Chamomilla recutita) and horsetail (Equisetum arvense) in three doses (150cc/ lt-1 , (300 cc/lt-1) and (0cc/lt-1), in three different environments of Quito (l1: Santiago; l2: Ecuadorian; l3: Guamaní), for which it was proposed to identify the main foliar diseases present in the crop and determine the best extract, the best dose and the interaction between these factors, as well as the economic analysis of Benefit/Cost for each treatment, using as a variable the incidence and severity of pests and the treatment costs From the data obtained, it was identified that the diseases present were the following Downy Mildew (Hyaloperonospora parasitica); black spot (Alternaria spp.); ringspot (Mycosphaerella brassicicola) and black rot of cruciferous vegetables (Xantomonas campestris) which presented an incidence of less than 25.44% and a severity of less than 1% compared to the controls with 84.96% incidence and 10% severity, respectively. The results obtained were: The evaluated plant extracts control foliar diseases of broccoli (Brassica oleracea var. Italica) in different environments in Quito. The vegetable extract of thyme (Thymus vulgaris) at a dose of 300cc/lt-1 presented the best rate of control of foliar diseases in Broccoli in urban environments of Quito, in the same way the extract of thyme (Thymus vulgaris) presented the best rate Benefit/Cost with 1.24.